A comparison of untreated and formaldehyde-treated barley distiller’s solubles and rapeseed meal as protein supplements in dairy cows given grass silage ad libitum - Huhtanen, Pekka; Khalili, Hannele; Näsi, Matti (Agricultural and Food Science, 1991)
Twenty Friesian cows in four pens were arranged in a 4 x 4 Latin square experiment with 4 wk experimental periods to evaluate the effects on feed intake, milk yield and milk composition of treating barley dried distiller’s solubles (DDS) with a formaldehyde reagent, and to compare DDS with rapeseed meal as a protein supplement in dairy cows given a grass silage-based diet. The control diet (C) consisted of grass silage ad libitum fed with 8.5 kg/d of concentrate based on barley, oats and barley fibre (250, 250 and 500 g/kg dry matter (DM)). In three other diets 1.5 kg/d of the basal concentrate was replaced with rapeseed meal (RSM) treated for reduced ruminal degradability, 1.5 kg of untreated DDS (UDDS) or 1.5 kg of DDS treated with formaldehyde reagent at the level of 15 l/t (TDDS). On average, protein supplementation increased silage and total DM intake by approximately 0.5 kg/d (P>0.05). Milk yield (P<0.1), protein content (P<0.05) and protein yield (P <0.01) were likewise increased. Untreated DDS had no effect on milk yield or milk composition as compared with diet C. Treatment of DDS with formaldehyde reagent tended to increase milk and protein yield as compared with UDDS, and resulted in a milk yield similar to that obtained with the RSM supplement. Compared with RSM, the mean milk protein yield was lower (P<0.01) when the diet was supplemented with DDS. Live weight gain was higher (P<0.05) in cows receiving RSM diet than in cows receiving DDS diets. Calculation of energy balance showed that increased milk energy output in cows fed diets containing protein supplements was mediated mainly through increased energy intake.